Preexisting chronic pain is not associated with moderate-to-severe acute pain after laparoscopic cholecystectomy: a prospective cohort study - Bishal Nepali; Asish Subedi; Krishna Pokharel; Ashish Ghimire; Jagat Narayan Prasad (PAIN Reports, 2024)
Abstract. Introduction:. We aimed to evaluate the relationship between preexisting chronic pain and acute postoperative pain after laparoscopic cholecystectomy (LC) and to identify predictors of acute postsurgery pain. Methods:. In this prospective cohort study, patients undergoing LC with general anesthesia were enrolled. The primary outcome was the incidence of moderate-to-severe pain during movement in the first 24 hours after surgery. Logistic regression analysed the association of perioperative risk factors with acute postoperative pain. Model performance was assessed using receiver operating characteristic curves (ROC), calibration belt plots, and 10-fold cross-validation. Results:. Of the 193 patients analysed, 49.74% experienced moderate–severe acute pain. Univariable analysis indicated that preoperative chronic pain increased the likelihood of acute postoperative pain (odds ratio [OR], 2.53; 95% confidence interval [CI], 1.40–4.55). Risk factors identified in the multivariable analysis were higher preoperative pain intensity (OR, 1.28; 95% CI, 1–1.65), sleep disturbances (OR, 1.42; 95% CI, 1.24–1.61), intraoperative fentanyl supplementation (OR, 3.68; 95% CI, 1.48–9.12), incision extension for gallbladder retrieval (OR, 7.27; 95% CI, 1.58–33.39), and abdominal drain placement (OR, 6.09; 95% CI, 1.08–34.34). Dexamethasone use was associated with reduced pain (OR, 0.05; 95% CI, 0.004–0.74). The model demonstrated strong discrimination (ROC = 0.909) and good calibration (test statistic = 0.02; P = 0.89). Cross-validation showed slightly lower accuracy (ROC = 0.896). Conclusions:. Preexisting chronic pain was not associated with acute postoperative pain following laparoscopic cholecystectomy. Significant predictors for acute pain included higher preoperative pain intensity, sleep disturbances, intraoperative fentanyl, incision extension, and abdominal drain placement, while dexamethasone use was associated with reduced pain.